2009
DOI: 10.1007/s11695-009-9887-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying of Semisolids and Pouch Motility Following Laparoscopic Adjustable Gastric Banding

Abstract: A standard normal gastric pouch emptying rate of semisolids in asymptomatic patients after LAGB was established. Postoperative prolongation of gastric emptying is a matter of mechanical delay without gastric pouch denervation. This study provides a first step of future functional evaluation of complications following this type of bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
9
2
Order By: Relevance
“…In contrast to previous studies we did not identify any evidence of retention within the supraband stomach [19,20,27]. It is most difficult to accurately determine the location of the LAGB without this anatomical resolution and this may explain different results obtained by others.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies we did not identify any evidence of retention within the supraband stomach [19,20,27]. It is most difficult to accurately determine the location of the LAGB without this anatomical resolution and this may explain different results obtained by others.…”
Section: Discussioncontrasting
confidence: 99%
“…Two recent studies have, however, suggested there is prolonged emptying of the pouch of stomach above the LAGB [19,20]. Sustained focal distension of the cardia with linear pouch emptying over minutes to hours could be expected to generate signals of satiety.…”
Section: Introductionmentioning
confidence: 99%
“…We found no differences in any of the mentioned parameters before compared to after LAGB, indicating that the procedure, unexpectedly, has no impact on gastric emptying for liquids. The acetaminophen absorption test is not recommended to evaluate gastric emptying for solid meals, which in other studies has been measured using scintigraphic methods [9,32,33]. However, with the liquid state of the oral glucose load used in standard diagnostic OGTTs in mind, we found the acetaminophen absorption test appropriate to measure gastric emptying in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…The "gold standard" for evaluation of glucose (in)tolerance is the diagnostic 75 g-oral glucose tolerance test (OGTT) [7], which is rarely used. The reason for this is most likely derived from an assumption that LAGB incurs slowing of gastric emptying that potentially, in itself, affects oral glucose tolerance [8,9], thereby introducing a potential bias in diagnostic results. Therefore, in order to clarify the applicability of OGTT to measure the impact of LAGB on glucose metabolism, we investigated the impact of LAGB on gastric emptying for liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and complete delivery of a semisolid meal to the infraband stomach refutes other data that propose supraband retention with a definable emptying half-time as the mechanism of satiety following LAGB [25,26]. Whilst liquids may be able to passively trickle past the resistance of the LAGB, how could solids or semisolids pass across the LAGB over a 30-min period?…”
Section: Discussionmentioning
confidence: 87%